Regional monetary policy - Rodríguez Fuentes, Carlos J. (Milton Park, Abingdon, Oxon ; New York : Routledge, 2006)
This book provides a comprehensive theoretical framework to explore the ways through which money and monetary policy may affect regions. It also utilizes a unique framework built upon the basic principles of the post Keynesian monetary theory which enables the identification of a new way for money and monetary policy to have a regional impact: the behavioral effect.
Includes bibliographical references (p. [160]-188) and indexes.
nmn 7/06/13
Loans
Keywords: Monetary policy; Regional economics; Spain